The effect of different onset thresholds on isometric hamstring force-time variables using force plates - Ripley, N.; Fahey, J.; Comfort, P. (Journal of Applied Sports Sciences, 2025)
Introduction. There is an increasing frequency of single joint isometric assessments using force plates within team sports to inform training decisions; however, limited methodological consistency has been identifi ed within the literature, including onset threshold (muscle contraction initiation). Purpose: The purpose of this study was to determine the eff ect of diff erent onset thresholds on force-time characteristics during a 90:90 isometric hamstring assessment. Methodology: Twenty female soccer players (age: 20.7 ± 4.7 years; height: 168.7 ± 5.9 cm; body mass: 64.4 ± 6.7 kg) completed three maximal trials per limb. Five thresholds assessed, including fi ve standard deviations (SD) of system weight (SW, which included limb weight and any pretension) (SW5SD), SW plus 15 N (SW15N), and 10-, 20-, and 30% of SW. Results: Moderate relative reliability and excellent absolute reliability for force at 100 ms (F100) and 200 ms (F200), and rate of force development (RFD) was observed for SW5SD and SW15N, outperforming percentage-based thresholds. 10-, 20- and 30% of SW resulted in increased F100, F200, and RFD values, with large eff ects observed (n²p > 0.166). Conclusions: SW5SD and SW15N were identifi ed as the most reliable and consistent methods for assessing time-related force variables. Practical implications: Sport scientists, strength and conditioning coaches, and medical staff who regularly use isometric hamstring assessments to monitor training and return to sport objectives are recommended to use either SW5SD and SW15N thresholds to ensure valid and accurate results on the hamstrings force generating that can be used to inform training.